Emergencies in Hematology: Tumor Lysis Syndrome - Michail Michailidou, Evangelia (Clinical Medicine And Health Research Journal, 2023)
TLS (tumor lysis syndrome) is a serious consequence of haematologic malignancies and their treatment. The condition is defined by laboratory abnormalities alone (laboratory TLS) or in conjunction with clinical consequences such as renal failure, seizures, and arrhythmias (clinical TLS). Clinical TLS is a risk factor for increased morbidity and death in cancer patients, although it may be avoided. As a result, accurate prediction is crucial to the effective management of patients at risk for TLS, and it takes into account both disease characteristics (tumor kind and load) and patient factors (baseline renal insufficiency or hyperuricaemia). In low- and intermediate-risk individuals, water and allopurinol are used to prevent TLS, whereas rasburicase is used in high-risk patients.